(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology has encouraged the widespread use of computer networks, thus requiring every individual to have knowledge and skills related to computer networks, including an understanding of supporting applications. One of them is Cisco Packet Tracer, a computer network simulator designed to help users understand the concept of computer networks visually and interactively. Given its importance of understanding this application, encouraged us to carry out Community Service activities. The main objective of this activity is to optimize the use of information technology through training in the use of the Cisco Packet Tracer application, in order to support the teaching and learning process, especially in the field of computer networks. The methodology used in implementing this activity consists of three main approaches: direct observation, which is carried out by visiting partner locations to understand the conditions and needs of participants; direct training, namely providing materials and practice in using the Cisco Packet Tracer application; and evaluation and monitoring, which aims to assess the effectiveness of the training and the extent to which participants can apply the knowledge provided. The results of the implementation of this activity indicate that the training provided has made a positive contribution to improving the understanding of students of SMK Negeri 1 Empat Lawang, especially in the use of the Cisco Packet Tracer application and the process of installing and configuring computer networks.